The Study of the relationship of some Bio Kinematic indicators with testing the accuracy of the level of skill performance of the high spiking of volleyball players - Fleah Rumeeh, Ammar; Khaleel Ibrahim Alsudani, Atheer (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the research is to identify the value of some biochemical indicators with the accuracy of testing the level of skill performance of high crushing hitting among volleyball players and the relationship between them , and the research problem was embodied in the absence of a study of the relationship of some biochemical indicators with the accuracy of testing the level of skill performance of high spiking in order to reach the accuracy of performance Technical serving sporting achievement and is working to develop it because it is linked to the conditions the biomechanics correct associated with your performance, and adopted the researchers descriptive approach, the research sample included 12 players , underwent a test level of skill performance hit the overwhelming high among volleyball players MRK g 4 , was filming the adoption of a camera Type (CASIO At a high speed (120 p / s), the values of the search variables were extracted through imaging and using the kinematic analysis program ((Kinovea8.25The data results were presented, analyzed and discussed and the correlation value was extracted for the variables that are more consistent with the kinetic energy index of the trunk and the height, and the most important findings of the research were ( that increasing the efficiency of the kinetic energy of body parts, whether linear or rotational, has a positive effect on the speed of the body's launch. And then achieving a better achievement distance through the law of preserving the amount of movement and having a high impact on the technical performance of the research sample), and the researcher recommended (the importance has evolved capacity Players On investment Properties Bio Mechanical To body in a the shape the performance Artwork Correct, and use kinematic analysis periodically during the identification of the mechanical changes that occur upon the rise of the players).